Kombinator-Y untuk Melakukan Memoizing Fungsi Rekursif - Subandijo Subandijo (ComTech: Computer, Mathematics and Engineering Applications, 2012)
This article discusses how to find a solution of a recursive function such as Fibonacci or factorial numbers without repetition. Therefore, a recursive function is considered a fixed-point of non-recursive function. To calculate the fixed-point, we can use Y Combinator, a non-recursive functions to perform memoizing recursive function. This method can significantly reduce the execution time of recursive functions.